Antimutagenic Activities of Methanol Extracts of Some Endemic Astragalus Species - Ozbek, Tulin; Gulluce, Medine; Agar, Guleray; Adiguzel, Ahmet; Baris, Ozlem; Ozkan, Hakan; Sahin, Fikrettin (Asian Journal of Chemistry, 2010)
The present study was conducted to evaluate the antimutagenic activity of methanol extracts of Astragalus campylosema, A. cristianus, A. globosus and A. lineatus plants. The possible antimutagenic potential of different species was examined against mutagens sodium azide (NaN3), 9-aminoacridine (9AC) and 4-nitro-1-quinoline oxide (4NQO) in Salmonella typhimurium strains TA1535-TA1537 and TA1538 using standard plate incorporation assay. In order to assess antimutagenic effects of Astragalus species. The plants methanol extracts were done at the doses of 5, 0.5 and 0.05 μg/plate. Astragalus species tested have different inhibition rate on mutagenicity at the concentration between 0.05-5 μg/plate doses. The best activity was obtained from A. cristianus aerial and root extracts, respectively; 78 % (5 μg/plate); 64 % (0.5 μg/plate), 79 % (5 μg/plate); 40 % (0.5 μg/plate) on TA1538.